1996
DOI: 10.1016/s0092-8674(00)81375-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of TNF Receptor 1 Effector Functions: JNK Activation Is Not Linked to Apoptosis While NF-κB Activation Prevents Cell Death

Abstract: Through its type 1 receptor (TNFR1), the cytokine TNF elicits an unusually wide range of biological responses, including inflammation, tumor necrosis, cell proliferation, differentiation, and apoptosis. We investigated how TNFR1 activates different effector functions; the protein kinase JNK, transcription factor NF-kappaB, and apoptosis. We found that the three responses are mediated through separate pathways. Recruitment of the signal transducer FADD to the TNFR1 complex mediates apoptosis but not NF-kappaB o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

85
1,396
8
6

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,853 publications
(1,501 citation statements)
references
References 61 publications
85
1,396
8
6
Order By: Relevance
“…Gel mobility shift assay revealed that TNF-ainduced nuclear translocation of NF-kB was blocked in RR/DN-IkBa-H cells ( Figure 3a). In addition, consistent with recent observations that NF-kB activity is required for TNF-a-induced cell death in various cell types (Antwerp et al, 1996;Beg and Baltimore, 1996;Liu et al, 1996;Wang et al, 1996), TNF-a treatment in RR/DN-IkBa-H cells led to a massive cell death within 18 h, whereas parental Rat-1(Ras) and RR/DNIkBa-L cells were little a ected ( Figure 3b). The genomic DNA isolated from RR/DN-IkBa-H cells after TNF-a treatment also exhibited a characteristic DNA fragmentation and corresponding cytoplasmic extract was shown to be capable of activating procaspase-3 ( Figure 3c).…”
Section: Inactivation Of Nf-kb Leads To Growth Inhibition and Reducedsupporting
confidence: 91%
See 1 more Smart Citation
“…Gel mobility shift assay revealed that TNF-ainduced nuclear translocation of NF-kB was blocked in RR/DN-IkBa-H cells ( Figure 3a). In addition, consistent with recent observations that NF-kB activity is required for TNF-a-induced cell death in various cell types (Antwerp et al, 1996;Beg and Baltimore, 1996;Liu et al, 1996;Wang et al, 1996), TNF-a treatment in RR/DN-IkBa-H cells led to a massive cell death within 18 h, whereas parental Rat-1(Ras) and RR/DNIkBa-L cells were little a ected ( Figure 3b). The genomic DNA isolated from RR/DN-IkBa-H cells after TNF-a treatment also exhibited a characteristic DNA fragmentation and corresponding cytoplasmic extract was shown to be capable of activating procaspase-3 ( Figure 3c).…”
Section: Inactivation Of Nf-kb Leads To Growth Inhibition and Reducedsupporting
confidence: 91%
“…It was suggested that oncogenic proteins, by modulating the activity of downstream transcription factors, may activate a set of genes which inhibit transformationassociated apoptosis (Koumenis and Giaccia, 1997). NF-kB has been shown to play an important role in protection from cell death, presumably by regulating the expression of anti-apoptotic genes (Antwerp et al, 1996;Beg et al, 1996;Liu et al, 1996;Wang et al, 1996;Chu et al, 1997;Yamit-Hezi and Dikstein, 1998;You et al, 1997). In light of these observations, it has been reported that Ras activates NF-kB to prevent transformation-mediated cell death and this antiapoptotic activity of NF-kB may be important for Ras-mediated cell transformation and tumorigenesis (Mayo et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alterations in JAK/STAT signaling have also been strongly implicated in the pathogenesis of human CTCL (Nielsen et al, 1997;Zhang et al, 1996). Loss of the IkB-like activity of p100 NF-kB-2 could lead to enhanced anti-apoptotic activity in these cells as a result of constitutive NF-kB activity (Beg and Baltimore, 1996;Liu et al, 1996;Sonenshein, 1997;Van Antwerp et al, 1996;Wang et al, 1996). Further studies of additional tumor-associated mutations of NFKB2, as well as detailed studies of altered NF-kB target gene expression will be required to further elucidate the mechanisms by which altered NFKB2 products contribute to the development of CTCL and other lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The polyps are usually multiple and sessile but may appear as a confluent plaque. They are found throughout the duodenum with a predilection for the periampullary area.…”
Section: S J H Van Deventermentioning
confidence: 99%
“…Both TNF receptors can activate the transcription factor nuclear factor B (NF B) that induces transcription of a wide range of genes involved in inflammation. 1,2 TNFRI is a member of a family of death receptors that share a death domain that initiates programmed cell death (apoptosis). However, TNF receptor-mediated nuclear translocation of NF B protects against apoptosis, 3,4 and thus activation of TNFRI may both induce and prevent apoptosis, depending on the type and activation state of the cell.…”
mentioning
confidence: 99%